Evidence-based guideline: Neuromuscular ultrasound for the diagnosis of carpal tunnel syndrome - Cartwright, Michael S.; Hobson-Webb, Lisa D.; Boon, Andrea J.; Alter, Katharine E.; Hunt, Christopher H.; Flores, Victor H.; Werner, Robert A.; Shook, Steven J.; Thomas, T. Darrell; Primack, Scott J.; Walker, Francis O. (Muscle & nerve, 2012)
Introduction: The purpose of this study was to develop an evidence‐based guideline for the use of neuromuscular ultrasound in the diagnosis of carpal tunnel syndrome (CTS). Methods: Two questions were asked: (1) What is the accuracy of median nerve cross‐sectional area enlargement as measured with ultrasound for the diagnosis of CTS? (2) What added value, if any, does neuromuscular ultrasound provide over electrodiagnostic studies alone for the diagnosis of CTS? A systematic review was performed, and studies were classified according to American Academy of Neurology criteria for rating articles of diagnostic accuracy (question 1) and for screening articles (question 2). Results: Neuromuscular ultrasound measurement of median nerve cross‐sectional area at the wrist is accurate and may be offered as a diagnostic test for CTS (Level A). Neuromuscular ultrasound probably adds value to electrodiagnostic studies when diagnosing CTS and should be considered in screening for structural abnormalities at the wrist in those with CTS (Level B). Muscle Nerve 46: 287–293, 2012